Between Women, Throne, and Power: Religious Transformation in Kagaua Palu, 1600-1904 - Nuraedah, Nuraedah (History Department, Semarang State University and Historian Society of Indonesia, 2023)
This study examines the discourse of women, the throne, and power as a foundation for thinking that led to the transformation of religion in Kagaua Palu’s history from 1600 to 1904. Few studies on women reveal its connection with the change of Islam in Palu. This study uses a qualitative-historical method with heuristic stages, source criticism, interpretation, and historiography. The data sources for this research are colonial manuscripts, newspapers, and some utterances (oral information). The study shows that religious transformation drives tradition in Kagaua Palu to experience a shift, seen from the shifting matrilineal system to the patrilineal, even though this does not apply in general. In addition, the religious transformation has also led to a shift in local cultural awareness and the birth of a dynamic Islamic understanding that has opened the broadest possible access. In general, the To Kaili woman has become a pillar of the forerunner to the throne and power, accompanied by a religious transformation in Kagaua Palu. In conclusion, To Kaili women are essential in developing Palu Muslim society. That becomes a comparative narrative that erodes patriarchal nuances in Indonesian historiography.Keywords: Woman, Throne and Power, Religious Transformation, Kagaua PaluKajian ini mengkaji wacana perempuan, tahta, dan kekuasaan sebagai landasan pemikiran yang berujung pada transformasi agama dalam sejarah Kagaua Palu dari tahun 1600 hingga 1904. Beberapa kajian tentang perempuan mengungkap keterkaitannya dengan perubahan Islam di Palu. Penelitian ini menggunakan metode kualitatif-historis dengan tahapan heuristik, kritik sumber, interpretasi, dan historiografi. Sumber data untuk penelitian ini adalah manuskrip kolonial, surat kabar, dan beberapa ucapan (informasi lisan). Studi ini menunjukkan bahwa transformasi agama mendorong tradisi di Kagaua Palu mengalami pergeseran, terlihat dari pergeseran sistem matrilineal ke patrilineal, meskipun hal ini tidak berlaku secara umum. Selain itu, transformasi keagamaan juga telah menyebabkan terjadinya pergeseran kesadaran budaya lokal dan lahirnya pemahaman Islam yang dinamis sehingga membuka akses seluas-luasnya. Secara umum, perempuan To Kaili telah menjadi pilar cikal bakal tahta dan kekuasaan, disertai dengan transformasi agama di Kagaua Palu. Kesimpulannya, To Kaili perempuan sangat penting dalam membangun masyarakat Muslim Palu. Itu menjadi narasi komparatif yang mengikis nuansa patriarki dalam historiografi Indonesia.Kata kunci: Perempuan, Takhta dan Kekuasaan, Transformasi Keagamaan, Kagaua Palu